Geopolitical Risk and Firm Financing Decision: Can ESG Performance Act as a Buffer? - Darryl Philip Rakiman; Eric Wilson; Steven Wahyudi; Rita Juliana (International Journal of Energy Economics and Policy, 2026)
This study aims to examine effects of geopolitical tensions on firms' capital structure behavior and the role of ESG to navigate toward heightened tension between countries. We use 2460 companies across Asian continent ranging from 2016-2023, The authors choose Asian as a continent of interest because Asia holds an important place in terms of geographical location as the center of world’s economy. The study employes a panel data regression model, followed by two-step generalized method of moment (GMM) to address endogeneity and ensure robustness. This study found that companies will reduce their use of debt when geopolitical conditions arise. Conversely, companies will increase their cash reserves when geopolitical conditions are high. This study also analyzed how the interaction between GPR and ESG performance affects companies' use of leverage and cash reserves. The study found that companies with strong ESG performance will reduce their use of debt as a form of risk mitigation and maintain their corporate reputation. Conversely, companies with strong ESG performance will increase their cash reserves when geopolitical risks are high. This indicates that companies with strong ESG performance are more sensitive to geopolitical risks.